PENGARUH KINERJA KEUANGAN DAN TINGKAT SUKU BUNGA TERHADAP REAKSI PASAR - Permatasari, Bella Ayu; Kurnia, Kurnia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThe purpose of this research is to examine the influence of the financial performance i.e. The data in this research is the financial statements i.e. Return On Asset (ROA), Return On Equity (ROE), Debt to Equity Ratio (DER), Price Earning Ratio (PER), Earning Per Share (EPS), and interest rates to the stock return on companies which are listed in Indonesia Stock Exchange (IDX). The sample collection technique has been carried out by using purposive sampling method 32 property companies which have published their financial statements and their stocks have been traded actively in Indonesia Stock Exchange in 2012-2014 periods have been selected as samples. Therefore, there are 96 financial statements which meet the sample criteria. The data analysis has been carried out by using the multiple regressions and the independen variables i.e : Return On Asset (ROA), Return On Equity (ROE), Debt to Equity Ratio (DER), Price Earning Ratio (PER), Earning Per Share (EPS), and interest rates, and the dependent variable is stock return. The result of the research has found that Earning Per Share has significant influence to the company stock return whereas Return On Asset (ROA), Return On Equity (ROE), Debt to Equity Ratio (DER), Price Earning Ratio (PER), and the interest rates are insignificant in the model.Keywords: Financial performance, interest rates, stock return, multiple linier regressions.